Creativity of Elementary School 1 Pekanbaru Teachers in Learning Cultural Arts and Craft (SBDP) - Siregar, Lindasari; Budiwirman, Budiwirman; Ardipal, Ardipal; Syeilendra, Syeilendra (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
This study employed a qualitative research method and a descriptive approach to data collection. The mural decorations and the teachers in the school served as the study's subjects, while the study's objects included the subject matter of the mural decorations, the shape of the symbol, the color, and the composition of the mural art. The research and interviews were conducted in classrooms I through VI of SDN 1 Pekanbaru, which totaled 15 classes; of these, a sample of three classes was taken. Observational methods, in-depth interviews, and visual documentation all contributed to the collection of research data. Methods of qualitative and descriptive analysis were utilized in the study of the data. The findings revealed that the appreciation of mural art was due to the creativity of the teacher in terms of shape, color, line, illustration, and the theme that was raised. Specifically, the following was the theme that was raised: first, a teacher at SDN 1 Pekanbaru characterized a simple form of the elements of natural balance as a mural object. One of them is about the image of freshness and coolness given by nature, and the importance of preserving the surrounding natural environment, such as in the mural "Come on, Preserve Nature", which is on the wall decoration for class VI-B, and the mural art for class VB is entitled "Let's Respect and Appreciate Each other's Mural Art.